The Massachusetts Resolves (Oct. 29, 1765), reprinted in Prologue to Revolution: Sources and Documents on the Stamp Act Crisis, 1764-1766, at 56 (E. Morgan ed. 1959) - (:unkn) unknown (My University, 1765)
Resolved that Massachusetts subjects have the same rights as are present and essential for natural born subjects.
Keywords: GUARANTEED RIGHT